Promising Spaces’: Universities’ Critical-Moral Mission and Educative Function - McLean, Monica (Critical Studies in Teaching and Learning, 2023)
Attention has been drawn to  reduction of  universities’ purposes  to  serve  economic  interests only.  This  dissatisfaction  has  provoked thinking about  how  to reclaim a  critical,  moral  role for  universities in  society. Inspired  by contemporary  utopian  studies this paper brings together traditional   ideas   about   how   transmitting   university   knowledge   connects   to universities’ critical-moral  functions, Amartya Sen  and Martha Nussbaum’s  capabilities approach adapted for education, and Basil Bernstein’s  theories about knowledge distribution. Focusing  on  the  educative function,  the  aim  is to  develop  a  theoretically-informed  and practical vision of a university education which is both personally transformative and able to produce  critical  citizens  and  workers. Research evidence from two projects  on  university education reveals‘ promising  spaces’  (Cooper,  2014)in  which  to  realise  these  aims. I conclude  that  there is  reason  to  believe that the transmission  and acquisition  of knowledge and  understanding in  specific  fields is  key  to  preserving  and  recreating a critical-moral mission for  universities wherever  they  are  in  the  world,  even  though  current conditions  are inclement and unequal